Defining the Physical Education Class as a Non-athletic, Non-competitive Activity: Editor: Thomas H. Sawyer. Issue 8 (13th October 2017) - Sawyer, Tonya L.
Abstract : The issue in this case was whether participation in a weightlifting activity that fulfilled a physical education requirement, wherein students were not in competition with one another, constituted "participation in an athletic contest" pursuant to Oklahoma statute § 155(20).